قصة سيدنا موسى مع فرعون في سورة الأعراف: دراسة تداولية - الصادق، الشيخ محمد خالد (جامعة الأزهر - كلية اللغة العربية بجرجا, 2020)
القرآن كتاب عربي مبين يقرأ صوته بلسان عربي ويبين معناه باللغة العربية، ولكي يفسر كلم القرآن بلوغاً إلى معانيه لابد من تعرف جذور الكلمات لتبين أصول المعاني، وتفقه تصريفها تركيبا لتقاس عليه دلالات التصريف بحركاتها وحروفها، وتجويد نطقها وتقدير مكانها نحواً وإعراباً ووقعها معنىً وبلاغة في سياق الجمل لتنضبط دلالاتها بياناً وتتسق بداعتها جمالاً. والناظر لبعض مناهج التفسير للقرآن الكريم، يجدها تذهب ماسحة سطح المعاني الكلية لا تنزل بيانها إلى وجوه الحياة وحقائقها التي يجليها موقع التنزيل والخطاب، وأحياناً تركز على بيان بعض الفروع مبتعدة عن أصولها العامة، ومنها ما يركز على الظاهري في هدى المعاني، ومنها ما تصوب إلى بيان هديه لباطن الوجدان. ولذلك سأوضح كيف تجمع الدراسة التداولية الحديثة بين خير كل المناهج من حيث ما اقتربت من بيان القرآن، بعد تطور العلوم والحياة لعلنا نكسب جديداً من هدي القرآن، وبنشره للناس ترقياً مداوماً إلى الأنسب والأوفق والأتم في سيرة التفسير وقد وقع اختياري لسورة الأعراف لأطبق على قصة سيدنا موسى مع فرعون فيها المنهج التداولي. وينطلق هذا البحث من اشكالية مفادها: كيف يمكن الكشف عن البعد التداولي في الخطاب القرآني من خلال المفاهيم التداولية؟ وما مدى كفاية المنهج التداولي لدراسة الأسلوب القرآني؟ والدراسة ذات بعدين (نظري وتطبيقي) فالدراسة النظرية تركز الحديث عن التداولية والتعريف بسورة الأعراف والدراسة التطبيقية اختار فيها قصة سيدنا موسى مع فرعون أطبق عليها المنهج التداولي، وقد توصلت الدراسة إلى العديد من النتائج أهممها: الخطاب القرآني بعامة وفي هذه القصص في سورة الأعراف خطاب كوني يخاطب الإنسان في أي زمان ومكان، مع أننا نجد أن هذه القصص قد نزلت في واقع معين وخاطبت شخصيات معينة في زمنٍ معين.
Quran is the Arabic Perspicuous Book recited and interpreted in the plain Arabic language. To interpret the Quran in order to reach its elevated meaning, it is necessary to trace the epistemology of words and understand the derivations to make it a measurement in its derivations, intonations, sounds and pronunciation. It is also important to give it its proper place in grammar, syntax, semantics, rhetoric and aesthetics. Looking at the available approaches of Quran interpretations, it is noticed that some interpretations are artificial, not digging up the true meanings and comprehensive message of life as meant in the revelation. It is also true that some other interpretations are to some extent deeper, but either focusing on the branches or on the surface meanings and a few tried to reach the internal psyche. This paper is an attempt to clarify how to pragmatic studies embrace the advantages of many approaches that address the interpretation of Quran. This is due to advancements in knowledge that helped a lot in selecting what is the best in the interpretation of Quran. Surat AlAAraf has been selected as it is Madania revealed at the establishment of the civil society in Madinah when there was a crisis between the believers and disbelievers in a moment of observation from the Jews and hypocrites at a time of expanding of the number of subjects, discourses, places and times. There can be found a variety of phrasing, linguistic units, pragmatic arguments, narrations, stories, news and reports. This makes Surat AlAAraf a prope topic for a pragmatic study. The problem of this research is how to explore the pragmatic dimension in the Quranic discourse through the Speech Act Theory? The study tries also to explore the sufficiency of the pragmatic approach to study the style of Quran. The study consists of two parts one is theoretical and the other is practical. The theoretical study focuses on introducing Surat Albaqara and the pragmatic approach as well. The practical part discusses the stories in Suarat Albaqara and examines them against the pragmatic approach. The study followed the descriptive methodology drawing on the pragmatic approach.
Keywords: القرآن الكريم -- قصص اللقرآن -- موسى، عليه السلام -- فرعون -- سورة الأعراف